2020
DOI: 10.3390/medicina57010006
|View full text |Cite
|
Sign up to set email alerts
|

Synergies Radiotherapy-Immunotherapy in Head and Neck Cancers. A New Concept for Radiotherapy Target Volumes—“Immunological Dose Painting”

Abstract: The combination of immune checkpoint inhibitors and definitive radiotherapy is investigated for the multimodal treatment of cisplatin non-eligible locally advanced head and neck cancers (HNC). In the case of recurrent and metastatic HNC, immunotherapy has shown benefit over the EXTREME protocol, being already considered the standard treatment. One of the biggest challenges of multimodal treatment is to establish the optimal therapy sequence so that the synergistic effect is maximal. Thus, superior results were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…The concept of immunological-clinical target volume (ICTV) and irradiation of partial volumes, contradicting the classical theory of target volumes, was previously postulated by Mireștean and collaborators in the article ‘Synergies Radiotherapy-Immunotherapy in Head and Neck Cancers. A New Concept for Radiotherapy Target Volumes-“Immunological Dose Painting” [ 23 ]. Adjustments in the classical theory of target volumes also include the indication of elective irradiation of lymph nodes.…”
Section: The Volume Factormentioning
confidence: 99%
“…The concept of immunological-clinical target volume (ICTV) and irradiation of partial volumes, contradicting the classical theory of target volumes, was previously postulated by Mireștean and collaborators in the article ‘Synergies Radiotherapy-Immunotherapy in Head and Neck Cancers. A New Concept for Radiotherapy Target Volumes-“Immunological Dose Painting” [ 23 ]. Adjustments in the classical theory of target volumes also include the indication of elective irradiation of lymph nodes.…”
Section: The Volume Factormentioning
confidence: 99%
“…In the case of recurrent and metastatic head and neck cancers, anti-PDL1 therapy demonstrates the maximum potential of radio-sensitization of the tumor in case of concurrent administration. 87 Keynote001, Pacific trial, and PEMBRO-RT Phase 2 Randomized Clinical Trial are examples where RT was sequentially followed by anti PD1/anti-PDL1 antibody in the pulmonary malignance. All of them suggested RT prior to anti PD1/anti PDL1 antibody strategy enhance the tumor control and is well tolerated without increasing incidence of >grade 3 AE.…”
Section: The Timing Of Rtmentioning
confidence: 99%
“…Besides these, for recurrent and metastatic head and neck cancers, superior results were obtained for the administration of anti-CTLA4 immunotherapy followed by hypofractionated RT. 87 A phase I/II study 61 explored patients with metastatic castration-resistant prostate cancer and found ipilimumab concurrently combined with RT (a single dose of 8 Gy 24-48 h before the first ipilimumab dose) induce clinical antitumor activity with favorable disease control and manageable AEs. However, there are some retrospective researches dealing with the sequence of ICI +RT combination therapy and coming up with controversial results.…”
Section: The Timing Of Rtmentioning
confidence: 99%
See 1 more Smart Citation
“…Bortezomib, a proteasome inhibitor active in the treatment of multiple myeloma and mantle cell lymphoma, has been evaluated in cell lines in HNSCC HPV +, demonstrating its ability to restore p53 function and hypothetical restore radiosensitivity via p21/p53 transactivation. However, in combination with radiotherapy or chemotherapy with Cisplatin, Bortezomide has no radiosensitivity and chemo-sensitivity modulator effect on HNSCC HPV+ and HPV- cell lines [ 2 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ].…”
Section: P53 New Horizons For Head Neck Cancer Treatmentmentioning
confidence: 99%